Pests are queuing up to be found - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Oil palm and coconut pests. Biology, description and control methods Mariau D.(Cirad-cp), Cirad, 2000 ISBN 2 87614 437 9 Référence: 802 FF 360 Euro 54.90